SCH23390 and a humanized anti-cocaine mAb decrease the latency to cocaine-induced reinstatement of lever pressing behavior in rats that self-administer cocaine - Dakota B. Zinani; Jhanvi N. Desai; Andrew B. Norman (Scientific Reports, 2023)
Abstract In rats that self-administer cocaine, the latency to the reinstatement of lever pressing behavior induced by a single dose of cocaine is due to the time taken for cocaine levels to fall to the satiety threshold. The D1 dopamine receptor antagonist SCH23390, and the recombinant humanized anti-cocaine mAb h2E2 increase the cocaine satiety threshold and would be expected to alter the latency to reinstatement. Male rats acquired cocaine self-administration behavior on an FR1 schedule. These rats received a single injection of cocaine (12 µmol/kg i.v.) after an i.v. injection of SCH23390 or an infusion of h2E2 or vehicle. The latency to, and the duration of, lever pressing was measured but the presses had no consequence. SCH23390 decreased the latency to lever pressing consistent with dose-dependent increases in satiety threshold. The duration of lever pressing behavior was inversely proportional to the SCH23390 dose suggesting that SCH23390 also increased the cocaine compulsion zone. The mAb h2E2 also produced a similar decrease in latency to responding that gradually reversed over 2 weeks. SCH23390 and h2E2 had an additive effect on the decreased latency to cocaine-induced lever pressing. The single cocaine dose reinstatement paradigm within the context of the compulsion zone theory is a useful pharmacological bioassay system to explore potential pharmacotherapies for relapse prevention in cocaine use disorder.